El Libro del arte de cozina de Diego Granado Maldonado. Estado del arte. - DE BENEDETTO, NANCY (Scripta)
Not much has been written about diego Granado's cookbool and hypotheses and errors continue to circulate that basically depend on the lack of a criticale edition that clarifies the origin of the various parts of the text and, above all, that facilitates its reading. It is a very heterogeneous and somewhat chaotic text wchich I am faced here only to present a recognition of the most important questions regarding the treatment of its two main sources. On the one hand Granado plagiarizes Robert de Nola's Libro de guisados (1529) which edition we fix here. On the other he tranalates the main part of Bartolomeo Scappi's Opera (1570). The author's working method reveals various cultural and linguistic inconsistencies that have been observed in relation to the treatment of ichthionyms.